Electroreduction of molecular oxygen on preferentially oriented platinum electrodes in acid solution - Zinola Sánchez, Carlos Fernando (1994)
The oxygen electroreduction reaction was studied on two different preferentially oriented ((111)-type and (100)-type and on a conventional polycrystalline (PC) platinum rotating disc electrodes in acid solutions at 30 °C. At low overpotentials, Tafel lines of −0.060 V decade−1 were obtained on the three electrodes in oxygen-saturated 1.0m H2SO4 and 1.0m H2SO4 + y; m K2SO4 (0 ⩽y ⩽ 1). At high over-potentials the usual Tafel slope of -0.120V decade−1 was observed on both (111)-type and PC platinum electrodes in 1.0m H2SO4, whereas a slope of −0.165V decade−1 was found on (100)-type platinum. In oxygen-saturated 1.0m H2SO4 the surface coverage by O-containing adsorbates on (100)-type platinum was greater than on both (111)-type and PC platinum. Rotating ring-disc electrode data showed that a higher amount of H2O2 was produced on (100)-type platinum than on the other platinum surfaces. The overpotential against current density plots are influenced by the anion concentration depending on the type of preferentially oriented platinum.